A Comparative Study of the Most Commonly Used Metaphors in Covid-19 News Texts during the Outbreak and Peak of the Disease - Mansour Nikpanah; Mansoureh Delaramifar (مطالعات زبانی و بلاغی)
This study deals with comparing the metaphors in Persian news texts related to Covid-19 disease within the two periods of the initial outbreak and its peak in October 2020 based on the Frame Semantics Theory. This research is a descriptive-analytic research. To this end, by using the news texts in Keyhan and Shargh newspaper, 20:30 news and online news agnecies, ISNA and IRNA, the metaphors related to COVID-19 were selected. 600 metaphors in these texts were extracted through “Metaphor Identification Procedure” pattern suggested by Pragglejaz. Then, the metaphors placed in the “disease” semantic frame, and their frame elements were identified. Finally, the frequency of the most used metaphors including "Corona is war", "Corona is a natural phenomenon", "Corona is a travel" and "Corona is another living thing" in the two periods between the initial outbreak  and the third peak in October 2020 were determined. The SPSS software was used for data analysis, and data were compared with each other. The findings demonstrated that in the beginning of the disease outbreak, the "Corona is war" metaphor is the most used metaphor in news texts with 44% frequency. But, during its peak in October 2020 coinciding the beginning of the cold season, the "Corona is war" metaphor has the highest rate of use among metaphors with 83% frequency. The results showed that there is a significant difference between the use of "corona is war" metaphor in the beginning of the disease outbreak and the peak time of the disease in October 2020.